Growth performance of pigs infested with sarcoptic mange - Wooten, E.L.; Broce, A.B.; Blecha, Frank (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two trials were conducted to determine the effect of sarcoptic mange on growth performance of pigs. Results from previous experiments with weaned pigs artificially infested with sarcoptic mites indicated no alteration of growth performance (average daily gain, average daily feed intake, and feed efficiency) in infested pigs. Two trials were conducted to further evaluate the effect of sarcoptic mange on pig growth performance. The first trial used 36, 90-lb pigs artificially infested twice or once with sarcoptic mites. Twice-infested pigs had higher average daily gain and improved feed efficiency 6 weeks after infestation than non-infested pigs. No alterations of growth performance were observed during the final 4 weeks of the trial. The second trial used 36, 30-lb pigs infested twice with sarcoptic mites (but mange was not as severe as in the first trial), No differences in growth performance were noticed during the 4-week observation period. These results suggest that, at some levels of infestation, sarcoptic mange does not affect pig growth performance.
Keywords: Swine; Growth performance; Sarcoptic mange